Postpartum Blues and Its Determinants: Continuity of Care, Spousal Support, and A Sleep Quality Among Postnatal Women in an Urban Indonesia Setting - Ika Novita Sari; Tukimin Bin Sansuwito (Media Publikasi Cendekia Indonesia, 2026)
Postpartum blues is a prevalent yet underrecognized mental health condition among postnatal women, particularly in rapidly urbanizing settings. Comprehensive identification of its determinants is essential for designing targeted interventions. This cross-sectional study aimed to examine the predictive roles of sleep quality, spousal support, and continuity of care on postpartum blues among 96 postnatal women attending community health centres (Puskesmas) in Batam City, Indonesia, enrolled via consecutive sampling between January and June 2025. Data were collected using validated instruments, the Pittsburgh Sleep Quality Index (PSQI), Postpartum Partner Support Scale (PPSS), and Continuity of Care Index (COCI), and postpartum blues was assessed using the Postpartum Blues Questionnaire (PBQ-32). Data analysis included chi-square tests and multivariate logistic regression. A total of 67.8% of respondents experienced postpartum blues of varying severity. Multivariate analysis showed that poor sleep quality (aOR = 8.14; 95% CI: 2.63–25.17; p < 0.001), low continuity of care (aOR = 6.02; 95% CI: 2.01–18.03; p = 0.001), and minimal spousal support (aOR = 4.53; 95% CI: 1.52–13.51; p = 0.007) were significant independent predictors, with sleep quality being the most dominant factor. Parity and delivery method did not show a significant association. The model had strong explanatory power (Nagelkerke R² = 0.71). Postpartum blues are significantly influenced by the interaction of behavioural, interpersonal, and structural factors within healthcare. Integrated interventions targeting improved sleep quality, strengthening spousal support, and improving continuity of care are needed. Given the cross-sectional design, these findings are preliminary and require longitudinal or interventional validation.